Life‐threatening heat‐related illness with severe hyponatremia in an aluminum smelter worker. Issue 12 (24th October 2019) - Wesdock, James C.; Donoghue, A. Michael
Abstract: Heat stress is a recognized occupational hazard in aluminum smelter pot rooms. This is the report of an unusual and complex case of heat‐related illness in an aluminum smelter worker. The 34‐year‐old male US worker developed life‐threatening heat‐related illness in August 2018, on his first day back at work after a 7‐day absence. The worker initially presented with bilateral hand then all‐extremity cramping followed some hours later by a generalized seizure and acute mental status changes, including combativeness. Emergency room evaluation identified a serum sodium level of 114 mmol/L. Acute liver and kidney injury ensued along with profound rhabdomyolysis, with peak total creatinine phosphokinase level reaching over 125 000 units/L at 3 days post incident. Initial ventilatory support, careful fluid resuscitation, and electrolyte management were provided. Metabolic encephalopathy resolved. Complications included sepsis. After 5 days in the intensive care unit and eight additional days of inpatient management, observation, and the initiation of rehabilitation, the worker was discharged. Residual effects include polyneuropathy of upper and lower extremities and the postdischarge magnetic resonance imaging finding of a cerebellar lesion. Prevailing considerations in the differential diagnosis included exertional heat stroke and/or exertion‐associated hyponatremia with encephalopathy.